2020
DOI: 10.3390/su12198066
|View full text |Cite
|
Sign up to set email alerts
|

Spider Webs and Lichens as Bioindicators of Heavy Metals: A Comparison Study in the Vicinity of a Copper Smelter (Poland)

Abstract: This paper presents the comparison of heavy metals accumulation in spider webs from Agelenidae family (Eratigena atrica and Agelena labyrinthica) and lichens Hypogymnia physodes, exposed to pollution for two months. Webs were obtained from the laboratory-reared spiders and stretched on Petri dish while lichens were transplanted from Stobrawa Landscape Park into the study area. Concentrations of Cu, Zn, Ni, Pb and As were determined in both biomonitors and the elevated values indicated the impact of the copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…The total concentration of Cu in the Cladonia pyxidata was found to be 3.10 ± 0.92 and 46 ± 14.4 for a sample collected from the forest and spoil mine heap, respectively (Table 2). These results are in good agreement with previous studies explaining the effect of the surrounding environment on the heavy metals accumulation in lichens [7][8][9][10][11][12][13][14]. On the other hand, the lowest concentration of Cu was found in Pseudevernia furfuracea collected from the forest site.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The total concentration of Cu in the Cladonia pyxidata was found to be 3.10 ± 0.92 and 46 ± 14.4 for a sample collected from the forest and spoil mine heap, respectively (Table 2). These results are in good agreement with previous studies explaining the effect of the surrounding environment on the heavy metals accumulation in lichens [7][8][9][10][11][12][13][14]. On the other hand, the lowest concentration of Cu was found in Pseudevernia furfuracea collected from the forest site.…”
Section: Resultssupporting
confidence: 92%
“…Lichens represent the dominant life form for about 8% of terrestrial ecosystems [1]. Recent studies have shown that Lichens species are widely used as biomonitoring for atmospheric heavy metals contamination [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In this region atmospheric aerosols can be characterized by the presence of Cu, Pb, Ni, Zn sulphides but also of metallurgical alloys varying in composition (Cu-Zn, Pb, Pb-Cu) [32]. Additionally, recent biomonitoring studies also provided the information about air contamination by Cu, Zn, and Pb in both of these regions [15,17]. In addition, an iron smelter-Małapanew in Ozimek can contribute to the air pollution by emitting the Fe particles to the atmosphere, however, from what is known for authors, now the activities in this area are much limited than in the past.…”
Section: Monitoring With Continuous Particulate Monitormentioning
confidence: 99%
“…Additionally, the method is noninvasive and can be considered no waste. The possibility of the use of spider webs in assessing air quality has been performed before, and satisfying results were obtained [13][14][15][16][17]. The webs have already proved to be a good passive sampler in the case of potentially toxic elements [13,16,18,19] or polycyclic aromatic hydrocarbons (PAHs) [20,21].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation